2007
DOI: 10.1002/ijc.22518
|View full text |Cite
|
Sign up to set email alerts
|

Gene transfer of the CD40‐ligand to human dendritic cells induces NK‐mediated antitumor effects against human carcinoma cells

Abstract: The CD40-ligand (CD40L) is a key molecule for the activation of dendritic cells (DCs), followed by the induction of DC maturation and cytokine production. Here we found that DC infected with adenovirus vector encoding human CD40L (CD40L-DC) displayed significantly higher levels of immune accessory molecules and IL-12 production than did uninfected cells, and that CD40L-DC produced much higher levels of IFN-c. To investigate whether CD40L-DC-derived these soluble factors could stimulate NK cells without physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…In an attempt to investigate the biologic function of the newly constructed CD154 mutant, we next constructed modified adenovirus vectors driving CD154-WT or CD154-M3 genes with the CA promoter/enhancer and incorporating the integrin-binding motif, RGD, into the HI loop of the fiber knob (AxCACD154-WT and Ax3CACD154-M3). 51 At the same multiplicity of infection, expression of transgenes such as LacZ and green fluorescence protein after infection of CLL-B cells with fiber RGD-modified adenovirus vectors were approximately 10 times higher than that obtained with adenovirus vector containing wild-type fiber knob (data not shown). Using these fibermodified adenovirus vectors, we transfected CD154-WT or CD154-M3 mutant into CLL-B cells and found approximately equal levels of CD154 on the cell surface.…”
Section: Discussionmentioning
confidence: 78%
“…In an attempt to investigate the biologic function of the newly constructed CD154 mutant, we next constructed modified adenovirus vectors driving CD154-WT or CD154-M3 genes with the CA promoter/enhancer and incorporating the integrin-binding motif, RGD, into the HI loop of the fiber knob (AxCACD154-WT and Ax3CACD154-M3). 51 At the same multiplicity of infection, expression of transgenes such as LacZ and green fluorescence protein after infection of CLL-B cells with fiber RGD-modified adenovirus vectors were approximately 10 times higher than that obtained with adenovirus vector containing wild-type fiber knob (data not shown). Using these fibermodified adenovirus vectors, we transfected CD154-WT or CD154-M3 mutant into CLL-B cells and found approximately equal levels of CD154 on the cell surface.…”
Section: Discussionmentioning
confidence: 78%
“…Using similar approach, CD40L transduced DCs enhanced the NK cell potential to kill various tumor cell lines. CD40L activated NK cells to express TRAIL and killed squamous cell carcinoma through TRAIL and granzyme-B [149]. DCs that were activated with CD40L transduced cell lines induced protective immune response against P815 mastocytoma upon loading with weakly immunogenic P1A tumor peptide of P815 mastocytoma in-vivo, which showed that CD40 induced efficient maturation of DCs [150].…”
Section: Cd40mentioning
confidence: 94%
“…Enhancing CD40L expression on DC cells, for example, enhanced NK-DC interactions and the maturation of DC, which in turn enhanced the production of appropriate cytokines that stimulated NK and enhanced the ability of these NK cells' cytotoxic ability toward certain tumor [43]. DC can also be activated by the innate recognitions of certain recombinant viruses or viral vectors (such as vesicular stomatitis virus, canarypox virus and adenoviral virus) to promote NK activation and prolonged antitumor immunity [44,45].…”
Section: Enhancing Nk-dc Crosstalk In Cancer Immunotherapymentioning
confidence: 98%